Rhabdomyolysis and acute kidney injury in the deceased donor: a case report - Zheng, Donghua; Liu, Hua; Zhan, Yaping; Xu, Guixing (International Journal of Research in Medical Sciences, 2019)
Rhabdomyolysis is a common complication among brain death donors, affecting the number of organ donations and the quality of donor kidneys. Case report: Male, 17 years old, admitted to the hospital due to a car accident. Subsequently, brown urine appeared, blood myoglobin increased significantly, urine output decreased, and renal function impaired. Treatments including fluid replacement, alkalization of urine, plasma exchange and bedside CRRT were given. The patient’s renal function recovered, and the organs were successfully acquired. The renal function recovered well after transplantation. Conclusion: Attention should be paid to rhabdomyolysis. Early diagnosis and treatment of patients with brain death could improve donation success rate and the recovery of postoperative renal function.